MiR‐181c Activates Mitochondrial Calcium Uptake by Regulating MICU1 in the Heart. Issue 24 (17th December 2019) - Banavath, Hemanth N.; Roman, Barbara; Mackowski, Nathan; Biswas, Debjit; Afzal, Junaid; Nomura, Yohei; Solhjoo, Soroosh; O'Rourke, Brian; Kohr, Mark; Murphy, Elizabeth; Steenbergen, Charles; Das, Samarjit
Abstract : Background: Translocation of miR‐181c into cardiac mitochondria downregulates the mitochondrial gene, mt‐COX1. miR‐181c/d −/− hearts experience less oxidative stress during ischemia/reperfusion (I/R) and are protected against I/R injury. Additionally, miR‐181c overexpression can increase mitochondrial matrix Ca 2+ ([Ca 2+ ]m ), but the mechanism by which miR‐181c regulates [Ca 2+ ]m is unknown. Methods and Results: By RNA sequencing and analysis, here we show that hearts from miR‐181c/d −/− mice overexpress nuclear‐encoded Ca 2+ regulatory and metabolic pathway genes, suggesting that alterations in miR‐181c and mt‐COX1 perturb mitochondria‐to‐nucleus retrograde signaling and [Ca 2+ ]m regulation. Quantitative polymerase chain reaction validation of transcription factors that are known to initiate retrograde signaling revealed significantly higher Sp1 (specificity protein) expression in the miR‐181c/d −/− hearts. Furthermore, an association of Sp1 with the promoter region of MICU1 was confirmed by chromatin immunoprecipitation‐quantitative polymerase chain reaction and higher expression of MICU1 was found in the miR‐181c/d −/− hearts. Conversely, downregulation of Sp1 by small interfering RNA decreased MICU1 expression in neonatal mouse ventricular myocytes. Changes in PDH activity provided evidence for a change in [Ca 2+ ]m via the miR‐181c/MICU1 axis. Moreover, this mechanism was implicated in the pathology of I/R injury. When MICU1 was knocked down in the miR‐181c/d −/− heart by lentiviral expression of a short‐hairpin RNA against MICU1, cardioprotective effects against I/R injury were abrogated. Furthermore, using an in vitro I/R model in miR‐181c/d −/− neonatal mouse ventricular myocytes, we confirmed the contribution of both Sp1 and MICU1 in ischemic injury. Conclusions: miR‐181c regulates mt‐COX1, which in turn regulates MICU1 expression through the Sp1‐mediated mitochondria‐to‐nucleus retrograde pathway. Loss of miR‐181c can protect the heart from I/R injury by modulating [Ca 2+ ]m through the upregulation of MICU1.